Analisis Faktor-Faktor yang Berpengaruh terhadap Kinerja Dokter di Rumah Sakit Umum Daerah Kota Dumai Tahun 2023 - Ratna Sari Lina; Ennimay, Ennimay; Ismainar, Hetty (Jurnal Kesehatan Komunitas, 2024)
Workload, job stress, and working environment conditions also influence doctors' performance in the hospital environment. The doctors' performance can be assessed by evaluating the quality of healthcare services provided to patients. In addition to the factors above, compensation is another factor that affects doctors' performance. Satisfaction with compensation, both in the form of adequate financial and non-financial rewards, can enhance work motivation. This study aims to analyze the factors influencing the performance of doctors working at the Dumai City Regional General Hospital and how these factors influence the performance of doctors at the Dumai City Regional General Hospital. This research is an analytical, quantitative, observational study with a Cross-Sectional design. The research was conducted at the Dumai City Regional General Hospital from July to August 2023. The population consisted of 72 individuals, and the sample size was 72 with the total sampling method. The inclusion criteria for the sample in this study were being a doctor by profession. Primary data in this research were obtained by filling out observation questionnaires and conducting interviews, while secondary data were obtained from documents available at the Dumai City Regional General Hospital. Data analysis was performed using multivariate analysis. The research results showed that motivation affects doctors' performance at a P value = 0.002 and POR = 3.667, while competency affects doctors' performance with a P value = 0.015 and POR = 1.372. In conclusion, motivation affects doctors' performance at the Dumai City Regional General Hospital, and competency also affects doctors' performance at the Dumai City Regional General Hospital.